Evasion Mechanisms Used by Pathogens to Escape the Lectin Complement Pathway - Rosbjerg, Anne; Genster, Ninette; Pilely, Katrine; Garred, Peter (Frontiers in Microbiology, 2017)
The complement system is a crucial defensive network that protects the host against invading pathogens. It is part of the innate immune system and can be initiated via three pathways: the lectin, classical and alternative activation pathway. Overall the network compiles a group of recognition molecules that bind specific patterns on microbial surfaces, a group of associated proteases that initiates the complement cascade, and a group of proteins that interact in proteolytic complexes or the terminal pore-forming complex. In addition, various regulatory proteins are important for controlling the level of activity. The result is a pro-inflammatory response meant to combat foreign microbes. Microbial elimination is, however, not a straight forward procedure; pathogens have adapted to their environment by evolving a collection of evasion mechanisms that circumvent the human complement system. Complement evasion strategies features different ways of exploiting human complement proteins and moreover features different pathogen-derived proteins that interfere with the normal processes. Accumulated, these mechanisms target all three complement activation pathways as well as the final common part of the cascade. This review will cover the currently known lectin pathway evasion mechanisms and give examples of pathogens that operate these to increase their chance of invasion, survival and dissemination.